2018
DOI: 10.1111/1750-3841.14211
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Antimicrobial Power of Low‐Effective Antimicrobial Molecules Through Nanotechnology

Abstract: Consumers demand for high-quality products, free from chemical preservatives, with an extended shelf-life. In this study, a really powerful antimicrobial agent based on a nanomaterial functionalized with a non-antimicrobial organic molecule was developed as a proof of concept. Following this approach it could be possible to develop a new generation of natural and removable antimicrobials based on their anchoring to functional surfaces for food, agricultural or medical purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…These studies demonstrated that the combination of the cell wall disruption capability of G3 dendrimer and the antibiotic effect of LVX into a unique MSNs-based nanosystem has a synergistic antimicrobial effect. Comparable results have been found for Gram-positive Listeria monocytogene by using polyamine-functionalized MSNs, as reported by Barat and co-workers [ 61 ]. The attractive forces between positive amine corona on MSNs and negative charges in bacteria membrane prompt cell membrane disruption.…”
Section: Targeted Delivery Of Antimicrobialssupporting
confidence: 75%
“…These studies demonstrated that the combination of the cell wall disruption capability of G3 dendrimer and the antibiotic effect of LVX into a unique MSNs-based nanosystem has a synergistic antimicrobial effect. Comparable results have been found for Gram-positive Listeria monocytogene by using polyamine-functionalized MSNs, as reported by Barat and co-workers [ 61 ]. The attractive forces between positive amine corona on MSNs and negative charges in bacteria membrane prompt cell membrane disruption.…”
Section: Targeted Delivery Of Antimicrobialssupporting
confidence: 75%
“…In general, the colour of the H. pylori cells remained green at the 0 h incubation time, which meant that cells were viable and membranes remained intact. In contrast, after 24 h of incubation with the EOCfunctionalised particles, the absence of cells or the presence of red-coloured cells indicated a damaged cell envelope, and eventual bacterial death (Ruiz-Rico et al 2018).…”
Section: Materials Characterisationmentioning
confidence: 90%
“…surface will confer antimicrobial properties to widely applied materials by creating antimicrobial functionalised materials. Previous studies have demonstrated that the immobilisation process allows the antimicrobial power of the attached molecules to anchor, concentrate and improve (Li and Wang 2013;Ruiz-Rico et al 2018), and can also prevent the limitations of free molecules.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study against L. monocytogenes G + was carried out by J. M. Barat et al [92]. Equivalent results were obtained when studying the effect of anchoring polyamines on the surface of MSNPs.…”
Section: Effect On Planktonic Bacteriamentioning
confidence: 77%